High serum vitamin D level correlates with better prognostic indicators in primary melanoma: A pilot study. (23rd March 2017) - Lim, Alvin; Shayan, Ramin; Varigos, George
Abstract: Background/Objectives: Sunlight is a major risk factor for cutaneous melanoma. However, its interaction with melanoma is complex. In particular, vitamin D is a UVB‐derived hormone that has been shown to have anti‐cancer effects. In this retrospective pilot study we sought to determine an association between the clinicopathological features of melanoma and the patients' corresponding serum vitamin D level. Methods: In total, 109 primary melanomas diagnosed between 2001 and 2013 were retrospectively identified from our institutional database with a corresponding 25‐hydroxyvitamin D3 level estimated within 6 months of diagnosis. Tumour, clinical (age, sex, tumour location) and pathological (thickness, mitosis, ulceration, Clark level, subtype, metastatic status) parameters were correlated with vitamin D. For statistical analysis, an unpaired Student's t ‐test andanova was used for categorical variables, and Spearman's correlation for continuous variables. Results: Vitamin D level was inversely associated with Breslow thickness as a dichotomous, categorical and continuous variable. The association remained significant when controlled for patient's age and sex ( P = 0.026). Vitamin D was higher in non‐ulcerated tumours compared with ulcerated tumours ( P = 0.006) and in tumours with mitotic rate <1/mm 2 compared with ≥1/mm 2 ( P = 0.036). A significant association was found between vitamin D level and tumour histological subtype ( P = 0.019). On subgroup analysis, significant associations were found between superficial spreading melanoma (SSM) and nodular melanoma ( P = 0.026), and SSM and acral lentiginous melanoma ( P = 0.007). Conclusion: A high vitamin D status may benefit prognosis in patients diagnosed with primary melanoma. A prospective cohort analysis with a large sample and controlled for other vitamin D confounders would validate these findings.